Bacillus megaterium and diatom improve mineral mining area soil quality and root biomass individually but show slightly inferior combined effects - Li, Yuyang; Pan, Jiachen; Shi, Xinran; Tang, Changxin; Zheng, Xuejia; Li, Chen; Zhao, Jinhua; Dong, Zhi; Wu, Qicong; Zhang, Congzhi (Frontiers in Plant Science, 2025)
Biological soil crusts (biocrusts) promote plant growth by improving soil structure and regulating soil nutrients. However, their effects on soil quality in mining subsidence areas remain poorly understood. The present study aimed to address this research gap by comparing the differences in soil nutrients, enzyme activities, soil quality, and plant growth following treatment with different types of biocrusts (control, diatom, Bacillus megaterium, and diatom-B. megaterium biocrusts) in mining subsidence areas. The results indicated that, compared to control biocrust treatment, individual treatment with diatom biocrust and B. megaterium biocrust significantly enhanced the organic carbon content, total nitrogen content, and invertase activity in the crust layer and increased the soil quality index values to 0.52 and 0.54, respectively. Diatom biocrust treatment was associated with a significant increase in ryegrass root biomass, which be linked to its improvement of soil structure. Ryegrass root biomass increased to 22.69 g, this effect was mediated by secretion of extracellular polymeric substances from the biocrust. In contrast, diatom-B. megaterium biocrust treatment increased crust roughness by 36.6% and improved soil moisture content by 18.7%, thereby further enhancing ryegrass root biomass. However, the diatom-B. megaterium biocrust treatment did not improve the soil quality index, despite increasing root biomass. Overall, these findings highlight the importance of applying biocrusts for soil remediation and plant growth in mining subsidence areas, providing a scientific basis for sustainable management and ecological restoration of degraded soils.